Design, Synthesis, and Biological Evaluation of Novel 1, 3, 4‐Thiadiazolylpyrazolines Compounds Containing Ferrocene. (2nd July 2018) - Chen, Liqin; Duan, Huihui; Zhang, Xinyu; Zhang, Qiong; Huang, Hailian; Zhao, Junlong; Chen, Bang; Hua, Chengwen; Gou, Xiaofeng
Abstract : The synthesis of 1, 3, 4‐thiadiazole skeleton compounds exhibiting high fungicidal activities has been demonstrated. Thirteen novel 1, 3, 4‐thiadiazolyl‐pyrazolines compounds containing ferrocene were designed and synthesized from the ferrocenylchalcones intermediates3a –3m and the 2‐hydrazino‐5‐phenyl‐1, 3, 4‐thiadiazole intermediate8 . All compounds were characterized by 1 H NMR, 13 C NMR, FT‐IR spectra, and HR‐MS, and the structure of one of the new compounds N ‐(4‐phenyl‐1, 3, 4‐thiadiazol‐2‐yl)‐3‐ferrocenyl‐5‐phenyl‐pyrazoline9a was further determined by X‐ray diffraction analysis. The preliminary results of a biological activity assay indicated that all the title compounds exhibited significant fungicidal activities against Pythium solani, Gibberella saubinetii, and Gibberella nicotiancola . Furthermore, compounds9e and9h displayed even higher fungicidal activities against the three fungal species compared with the control drug pyraclostrobin. Abstract :